Analisis Wacana Kritis dalam Program Televisyen Raja Lawak dan Implikasinya terhadap Psikososial Audiens di Malaysia (Jurnal Bahasa, 2012)
This article examines discourse in The Raja Lawak Series aired by ASTRO in early 2008. The use of critical discourse analysis in applied linguistics opens up a variety of approaches to understanding messages in the media. Critical discourse analysis approach proposed by Kress, Kaplan, Fairclough and Van Dijk is employed to analyse discourse within media and communication settings. This study tries to link the multidimensional structures of the discourse and their implications, particularly on the mental development of youths in more than 50 years after achieving independence. Two methodologies are used in the qualitative analysis of this television series, observation of the writer and documentary of textual analysis collated form verbal and non-verbal expressions.Keywords: satirical humour, psychosocial development, critical discourse analysis, multidimensional discourse, audiovisual